ESTIMATION OF THE RELATIONSHIP BETWEEN SOLAR RADIATION, RELATIVE HUMIDITY, AND TEMPERATURE IN UGWOLAWO USING LINEAR REGRESSION ANALYSIS (FUDMA JOURNAL OF SCIENCES, 2024)
The radiation of the sun has a critical climatic influence on solar energy generation, ecology and crop production. Consequently, it is important to know how solar radiation interacts with other climate variables such as temperature and relative humidity towards developing better designs of solar arrays and mitigate the impact of climate variability. In this study, we have explored the impacts of relative humidity and temperature on the sun’s radiation. The statistical data for this work was collected from the trustworthy National Aeronautics and Space Administration (NASA) power archive. Shortwave solar radiation, relative humidity and temperature readings from January 1991 to December 2020 were retrieved and evaluated to establish average values.  The results showed that the annual relative humidity ranged from 77.25% to 83.94%, while the annual temperature fluctuated between 24.86°C and 26.58°C, and the radiation from sun varied from 4.72 to 5.40 kW-hr/m². Both graphical and statistical analyses using a simple regression model indicated a slightly direct correlation between solar radiation and relative humidity while data regarding temperatures and solar radiation during the analysis period demonstrated an inverse relationship.
Keywords: Solar radiation; Relative humidity; Temperature; Simple regression method